Comments on the authorship, generic position, and synonymy of Diaeretiella rapae (M‘Intosh) (Hymenoptera: Aphidiidae). - Mackauer, Manfred (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The paper discusses authorship, generic position, and synonymy of Diaeretiella rapae (M'Intosh, 1855) (Hymenoptera: Aphidiidae). Evidence is presented for the authorship of Charles M'Intosh. Genus Diaeretiella Stary is shown to be closely related to genus Aphidius Nees. In addition, two new synonyms of Diaeretiella rapae (M'Intosh) are published: Lysiphlebus crawfordi Rohwer, 1909, and Diaeretus aphidae Mukerji & Chatterjee, 1949, the latter being an objective synonym of Diaeretus aphidum Mukerji & Chatterjee, 1950.Nomenclatural Actsaphidae Mukerji & Chatterjee, 1949 (Diaeretus), syn. n. of Diaeretiella rapae (M'Intosh, 1855)crawfordi Rohwer, 1909 (Lysiphlebus), syn. n. of Diaeretiella rapae (M'Intosh, 1855)